A Prospective Randomised Comparison of the LMA ProSeal™ versus Endotracheal tube on the Severity of Postoperative Pain following Gynaecological Laparoscopy. Issue 1 (January 2013) - Griffiths, J. D.; Nguyen, M.; Lau, H.; Grant, S.; Williams, D. L.
Pain and postoperative nausea and vomiting (PONV) are common problems after gynaecologic laparoscopy. Two recent studies have shown that morphine requirements and PONV are lower when a LMA ProSeal™ is used, rather than an endotracheal tube (ETT), for female patients undergoing breast and gynaecological surgery. We conducted a patient and observer-blinded randomised controlled trial, recruiting non-obese women without gastro-oesophageal reflux undergoing laparoscopic gynaecological surgery. Patients received a standardised relaxant general anaesthetic and then were randomised to receive either an LMA ProSeal or an endotracheal tube. Patients were assessed at two and 24 hours post-anaesthesia. The primary outcome was postoperative pain score and secondary endpoints included morphine consumption, postoperative emesis and adverse upper airway symptoms. We recruited 116 patients to the study, 57 patients in the ETT group and 59 patients in the LMA ProSeal group. The patients were similar in demographic and surgical characteristics. At two hours, the ETT group was similar to the LMA ProSeal group in regards to pain scores (verbal rating scale 3.0 vs 3.5, P =0.86), morphine consumption (7.2 vs 7.4 mg, P =0.56) and PONV (47.4 vs 47.5%, P =0.99). After 24 hours, pain scores and PONV rates were also similar. No significant difference in rates of sore throat or dysphagia was observed between the ETT and LMA ProSeal groups. No significant complications were attributable to either airway device. The LMA ProSeal did not decrease pain or PONV in patients undergoing gynaecological laparoscopy when compared to endotracheal intubation.